Hubungan religiositas dengan social media addictions pada mahasiswa Universitas Muhammadiyah Prof. Dr. Hamka - Nur Peni, Wike; Mundzir, Ilham (Indonesian Journal of Counseling and Development, 2024)
Excessive social media use among students has been linked to detrimental impacts on mental, physical, and academic well-being. This study investigated the relationship between religiosity and social media addiction among 102 college students Universitas Muhammadiyah Prof. Dr. Hamka. Employing an accidental sampling technique, data were collected using the MUDRAS religiosity scale and a modified social media addiction scale. Data analysis was carried out using the Pearson correlation test in SPSS 20. Pearson correlation analysis revealed a significant negative correlation (-0.212) between religiosity and social media addiction, suggesting that higher levels of religiosity are associated with lower levels of social media addiction. These findings support the notion of religiosity as a potential protective factor against this prevalent issue. Future research should explore this relationship in greater depth to develop effective prevention and intervention strategies